How to include key competences in the course plan - García Peinado, Benito (Avances en Supervisión Educativa, 2009)
In our school we have decided to develop the teaching approaches to key competences through an organizational model that could be called "the model of the educational basic training". When suggesting new planning, we think that we must offer some solutions which start from the classroom routines and help us to choose the best aspects of these methods to improve them.